Analisis Regangan di Selat Sunda berdasarkan Data GNSS - Ongky Anggara; Satrio Muhammad Alif; Danda Selfa Januarta; Yoga Maulana (Universitas Andalas, 2026)
The Sunda Strait is a complex tectonic transition zone between Sumatra and Java, influenced by the interaction between the Indo-Australian and Sundaland plates. This study aims to analyze interseismic displacement patterns and strain accumulation using continuous Global Navigation Satellite System (GNSS) data observations spread across southern Sumatra, the Sunda Strait, and western Java. The analysis results show that GNSS stations along the west coast of Sumatra experience significant shifts to the northwest at varying speeds, reflecting the direct influence of subduction. Meanwhile, stations in the West Java region show a more uniform shift pattern to the southeast. In the Sunda Strait region, a complex displacement pattern is identified, influenced by a combination of tectonic cessation and volcanic activity, particularly around Mount Anak Krakatau. The results of strain accumulation amounted to 50 nanostrains per year in the tectonically active region. These findings indicate that the Sunda Strait region has high tectonic activity potential and plays an important role in the release of seismic energy in the future. Therefore, continuous geodetic monitoring is essential to support the understanding of cooling processes and disaster mitigation efforts in this region.